Identification of fertility restorers among Assam rice cultivars by phenotyping and molecular screening approaches - Singh, Arun Kumar; Borah, Pulin; Ponnuswamy, Revathi; Sarma, Debojit; Roy, Ashutosh; Hazarika, G.N. (The Indian Journal of Genetics and Plant Breeding, 2016)
In three line hybrid rice seed production the combination of a CMS line, maintainer line and restorer line are involved in the development of hybrids. The wild abortive CMS is extensively used in commercial hybrid seed production. The fertility restoration of wild abortive CMS is governed by two independent dominant Rf genes viz., Rf4 and Rf3. The present study was conducted with the objective of molecular characterization rice genotypes from Assam, India and to identify restorers for hybrid rice breeding programme. A total one hundred and eleven hybrids were generated and evaluated for their pollen and spikelet fertility. Based on molecular screening twenty five genotypes were identified to carry only Rf4 gene and three genotypes identified to carry both Rf3 and Rf4 genes. These identified restorers in the present study would be a usable restores for hybrid rice breeding in north east India. Molecular diversity for fertility restoration using NTSYS package formed two clusters among the tested genotypes, cluster A represented a landrace Terabali from Assam and cluster B with all other genotypes.